PENGARUH DISIPLIN DAN MOTIVASI TERHADAP KINERJA KARYAWAN - Eris Harismasakti; Nurhayati Nurhayati (The Asia Pacific Journal Of Management Studies, 2019)
Employee performance in a company are expected to improve good performance to realize the goals in the company. Thus for the creation of good performance there needs to be an application of attitude to employees. Discipline and motivation are needed in every employee, the implementation of tasks or activities in the company’s work cannot run well and smoothly, so that it can ultimately harm the company itself. Discipline is the attitude of willingness and willingness to meat and obey the norms that apply around it. Motivation is the desire in a person that causes the person to act. The purpose of this research is to know the influence of descipline and motivation to the of PT.INDAH KARGO MANDIRI  RangkasbitungEfforts to improveThe research method used is descriptive method using a quantitative approach, i.e. to explain a problem based on the data in the form of figures (statistical data). The population used in this study is that PT. INDAH KARGO MANDIRI Rangkasbitung with 117 the number of visitors, using the formula error level slovin 5% then the sampael obtained as many as 97 consumers. The technique of data collection is the observation, study of librarianship and the questionnaire. Data analysis technique used is multiple regression analysis, correlation analysis, multiple coefficient of determination, t-test and f-test.Based on the research conducted, obtained test results t that brand image (X 1), namely the significant level of significant extent < (0.027 < 0.05). So starting in H0 and Ha accepted and significant value of the obtained motivation (X 2), namely the significant level of significant extent < (0.000 < 0.05). So starting in H0 and Ha is received. That means there are influences between the discipline Of PT.INDAH KARGO MANDIRI Rangkasbitung  and there is the influence between motivation Of PT.INDAH KARGO MANDIRI Rangkasbitung. As well as the results of hypothesis testing the F value obtained significant i.e. 0.000 value smaller than 0.05 significant level. Or F-count is greater than the F-table (0, 11.534 > 0, 3.94). Then it can be inferred that the brand image and product quality influence on purchasing decisions simultaneously.